2010
DOI: 10.1007/s00420-010-0564-9
|View full text |Cite
|
Sign up to set email alerts
|

Duration of wet work in hairdressers

Abstract: According to the guidance of the German Federal Ministry for Labour and Social Affairs, hairdressers should get a possibility for targeted occupational-medical health examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 11 publications
2
24
0
1
Order By: Relevance
“…A German observational study found that hairdressers were exposed to wet work, defined as having wet hands or wearing protective gloves, for an average of 2 h and 17 min in an 8 h shift 48. Fewer apprentices in the intervention group in the present study reported wet hands for 2 h or more per day compared with the control group (p=0.004) while working in the salons (table 3).…”
Section: Discussionmentioning
confidence: 42%
“…A German observational study found that hairdressers were exposed to wet work, defined as having wet hands or wearing protective gloves, for an average of 2 h and 17 min in an 8 h shift 48. Fewer apprentices in the intervention group in the present study reported wet hands for 2 h or more per day compared with the control group (p=0.004) while working in the salons (table 3).…”
Section: Discussionmentioning
confidence: 42%
“…In other words, there was no significant difference in the risk of hand eczema in the hairdressers with and without university education, and also with hand washing less than 20 times or more than 20 times a day. Kralj et al found that on average in a 8-hour work shift, hairdressers performed 2 hours and 17 minutes of wet work [31]. According to Uter et al, wet work can be considered as a major risk factor for hand eczema, when it lasts more than 2 hours a day [15].…”
Section: Discussionmentioning
confidence: 99%
“…In considering whether hairdressers are actually exposed to an extended duration of wet work, one report suggested that hairdressers are exposed to more than 2 hours of wet work per day and that exposure time was longer in master hairdressers than in apprentices [5], while another report suggested that wet work duration is related not only to washing but also to water-resistant glove wearing tasks such as dyeing or giving permanent waves [24]. Likewise, as a result of prolonged exposure to chemicals and water, the occupational group with the highest annual incidence rate (120 cases per 100,000 employed) of occupational contact dermatitis was reported to be female hairdressers and barbers [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hairdressing involves certain amounts of repetitive movement of the hands or arms [3,4]. In addition to these risk factors, hairdressers are also exposed to prolonged wet work [5] since a considerable portion of hairdressers’ tasks involves water-resistant glove wearing or direct contact with water [6]. There have been some previous studies regarding health issues in hairdressers in Korea, such as musculoskeletal disease [7], chemical exposure [8] or dermatologic disease [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation